THE MORAL CALCULUS OF PHARMA COMPANIES IN INDIA - MOTHA L, CRESENTA SHAKILA; R, Nalini; R, ALAMELU; R, AMUDHA (Asian Journal of Pharmaceutical and Clinical Research, 2016)
To comprehend whether corporate social responsibility (CSR) in pharma is more of a corporate hypocrisy where firms and organizations tend to marginalize their employees and the environment at large. The present study is case based, and an attempt has been made to analyze probable driving reasons behind the corporate behavior exhibited by pharma industries. CSR is understood differently by different beneficiaries but usually refers to serving the citizens, population of communities, and the larger society in a way that goes beyond what is legally required of a firm. Though numerous programs and schemes have been launched for their upliftment, it is all an eye wash which is intended for the internal benefit of the organization. Corporate these days, as per the Companies Act should report spend of 2% of their profits as pronounced in the CSR and pharmaceutical companies are no exemption to it. As per Section 135 of the Companies Act 2013, it is recommended that companies having revenue above Rs. 1,000 crore and profit more than Rs. 5 crore should report what they spend for CSR. Companies these days often utilize CSR as a brand building exercise, engagement of employees, helping the local community around their firm, or even as a fame generating spot for the themes of the chairman's spouse. Thus, it is obvious that the social responsibility of pharmaceutical business sector is mainly to increase their profit, increase their shareholder activism, and investment in the community. Keywords: Corporate social responsibility, Hypocrisy, Pharmaceutical industries, Society and organization.